Preparation of Flexible Substrate Electrode for Supercapacitor With High-Performance MnO2 Stalagmite Nanorod Arrays - Ge, Yuanyu; Wang, Xianfeng; Zhao, Tao (Frontiers in Chemistry, 2019)
A large-area MnO2 stalagmite nanorod arrays (SNAs) growing vertically on flexible substrates were successfully fabricated by an easy heat-electrodeposition method. The large specific capacitance (646.4 F g-1 at 500 mA g-1) and excellent rate capability (42.3% retention with 40 times of increase) indicate that the prepared MnO2 SNAs flexible electrode has outstanding electrochemical performance. Furthermore, after 5000 repetitions of CV tests, the overall specific capacitance could retain ~101.2% compared with the initial value meant a long cycling life. These outstanding properties could be ascribed to the effective conductive transport path between Ni substrate and MnO2 nanorods, and owing to the stalagmite like structure of MnO2 nanorods, the exposed sufficient active sites are beneficial to the electrolyte infiltration.